A proposed computer program to assess teaching skills of computer teachers in Sulaimani University according to the Bologna Process - خالد, أ.م.د حسن فخر الدين خالد; محمود, يادكار محمد فرج محمود (Sulaimani Journal for Humanities, 2025)
The aim of this research was to design a proposed computer program to evaluate the teaching skills of computer instructors at the University of Sulaimani, based on the Bologna Process. The researcher followed the experimental approach, where the research community included all computer instructors in the computer science departments at the University of Sulaimani for the academic year (2021-2022), totaling (89) male and female instructors, including (51) male and (38) female instructors. The research sample was selected intentionally, where instructors from the College of Basic Education - Department of Computer Science were selected, with the research sample consisting of (12) male and female instructors, comprising (9) male and (3) female instructors. Drawing on the insights of previous studies, the researcher used two tools to collect and analyze data: 1) an assessment form to obtain data and 2) a computer program to evaluate data, both of which were developed by the researcher himself. After verifying validity and reliability, the evaluation was conducted. The primary statistical tools used in this research included the arithmetic mean, standard deviation, Pearson's correlation coefficient, and Cronbach's alpha. The results showed high levels of teaching skills, including planning, implementation, evaluation, and feedback, among the selected sample members. Furthermore, no statistically significant differences were found among sample members based on gender in the quality of teaching skills. In light of the research findings, the researcher formulated and proposed several recommendations to enhance the evaluation practices of computer science teachers in the College of Basic Education.
Keywords: Computer Program; Assessment; Teaching Skills; Bologna Process